PENGARUH PENGGUNAAN METODE TUTORIAL TERHADAP PENINGKATAN NILAI BELAJAR SISWA PADA MATA PELAJARAN AQIDAH AKHLAK DI KELAS VIII MTs TA’DIB AL-MUALLIMIN AL-ISLAMY TAHUN AJARAN 2021-2022 - Salim Said (Fakultas Agama Islam, 2021)
The value of students' moral aqidah lessons is still relatively low at MTs Ta'dib Al-Muallimin Al-Islamy, the low values of moral aqidah lessons in general are on average 6-7 and only a few have 8 learning scores. the learning method applied by the aqidah moral teacher, because the learning method applied so far still seems conventional or the lecture method, question and answer and assignment. Therefore it is considered important to use the tutorial method. The purpose of this study was to determine the use of the tutorial method in the student learning process on the subjects of aqidah morality. This study aims to determine the learning value of Aqidah Morals subjects at MTs Ta'dib Al-Muallimin Al-Islamy and to determine the effect of using the tutorial method on increasing student learning scores in Aqidah Morals subjects at MTs Ta'dib Al-Muallimin Al-Islamy. This research method is quantitative with a sample size of 30 people. This research method used quantitative method by setting a sample of 30 people. The results of this study indicate that the use of the tutorial method in learning morals for students in class VIII MTs Ta'dib Al-Muallimin Al-Islamy Year 2021-2022 is implemented well, this can be seen from the implementation of the tutorial model learning accepted and liked by students, namely the system teacher's guidance. The learning scores of class VIII MTs Ta'dib Al-Muallimin Al-Islamy based on the test given after being taught the tutorial method learning model with an average value of 10.16, while the standard deviation of 8.60 and the price variance 2.93. there is a difference between the tutorial method and the conventional model on the value of learning moral aqidah education in class VIII MTs Ta'dib Al-Muallimin Al-Islmy with a comparison that the tutorial method is higher than the conventional method. 1,667. This means that accept Ha or reject Ho, which means the average learning value of students who are taught with the tutorial learning model is higher than the average learning outcome of students who are taught using conventional learning strategies.